ANALISIS PENGARUH MANAJEMEN RISIKO TERHADAP PROFITABILITAS (Studi Komparatif Pada Bank Umum Konvensional dan Bank Umum Syariah yang Terdaftar di OJK Periode 2012 – 2015) - Hafidz Ridho Ansori; Safira Almunawar (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2018)
Risk management is a good potential events that can be predicted and unpredicted negative impact on income and capital of the Bank. Financial ratios are an alternative to test whether financial ratios useful for making predictions on future profitability. CAR, NPL and LDR is a measure of the ability to predict profitability. Sampling technique used is purposive sampling with criteria Conventional Commercial Bank do / unlock (Dual Banking System) Islamic Banks serving the financial statements of the period 2012 to 2015. The data obtained by the publication of the FSA Directory. Obtained a total sample of 16 with the division 8 8 Conventional Commercial Bank and Commercial Bank Syariah. The independent variables in this study is the Capital Adequacy Ratio (CAR), Non performace loans (NPLs) and loan to deposit ratio (LDR) while Return on Assets (ROA) as the dependent variable. Methods of data collection in this study is documentation and literature. During the period show that the study data were normally distributed. Based on the test multicollinearity, heteroscedasticity test and autocorrelation test found no deviation from the classical assumption, it indicates that the available data are qualified to use a multiple linear regression model. The comparison of this study showed that the CAR and NPL variable Conventional Commercial Bank affect the ROA, LDR whereas no effect. In contrast to the conventional, all variables Islamic Banks are CAR, LDR and NPL effect on ROA.